Dolerite control on the distribution of high-grade iron orebodies at Assen Iron Ore mine, South Africa - Negwangwatini, Elekanyani Shadrack (My University, 2021)
The Assen Iron Ore deposit is located in the Crocodile River Inlier which lies within alkali rocks of the 2.05 Ga Bushveld Igneous Complex (BIC). The host rocks to the Assen Iron Ore deposit are contained in the lower portion of the Penge Formation of the Transvaal Supergroup, close to the contact with the underlying dolomite of the Malmani Subgroup. This study presents a detailed geological mapping of the Assen Iron Ore deposit. Petrographic and mineral characteristics of different iron ore facies and the dolerite intrusions from three iron ore mineralised portions named west, middle, and east orebody were conducted. The study investigated whether the intrusions control the mineralisation of high-grade iron orebodies. The different types of hematite and dolerite intrusions were sampled from the Assen Iron Ore mine's current operating pits and analysed using X-ray powder diffraction (XRD) and optical microscopy. Existing X-ray fluorescence (XRF) from the previously drilled diamond cores were used to compare and correlate different oxides with different iron ore facies. The banded iron formations (BIFs) that constitute the Penge Formation in the Assen area comprise several stratigraphically conformable rocks, namely shale, limestone, and mineralised units represented by calcitic hematite, high-grade hematite ore (i.e., laminated, and massive hematite ore), and goethite-rich hematite ore. The shale forms a basal layer consisting mainly of chert-rich BIF lenses with pyroclastic and tuffaceous sections. The intermediate layer with micro-and meso-layering consists of hematite and calcite, typical of carbonate facies. A high-grade hematite-rich ore directly overlies the calcitic ore. Lying above the high-grade hematite is atypical goethite-rich ore with grades between 50 to 55 % Fe. Detrital iron ore is located at the base of the southern slope of the Assen ridge. This ore is unconsolidated and occurs as small, rounded cobbles and pebbles of iron-rich sandy sediment from 1 m to 2 m thick. The geological mapping and exploration drilling indicate that the orebodies are structurally controlled along the dolerite sills that intruded the BIF sequence of that Transvaal supergroup. At places, goethite-rich and laminated hematite are found above or on the hanging wall of the dolerite sills. Massive hematite tends to be underlain the dolerite. Calcitic hematite is always located in the stratigraphy below massive and laminated hematite and is underlain by either the dolerite on the edge of iron formation or shale. At Assen Iron Ore mine, dolerite sills intruded the BIF of the Penge Formation. Post-deposition and intrusion, both the dolerite intrusions and BIF were affected by the three stages of folding (F1, F2, F3-folds) and faulting which caused deformation and partial metamorphism. Thermal metamorphism is associated with the BIC which surrounds the Inlier and resulted in alteration of primary minerals, change in bulk rock chemistry, and visual appearance of the rocks. The XRF analysis showed the downward increases in % iron (Fe), downward decrease in silica (SiO2) in both BIF, goethite, laminated and massive hematite. The calcitic hematite showed a downward decrease in iron (Fe) and a downward increase in calcium (Ca). The laminated hematite (55-59 % Fe) and high-grade Fe in BIF (50-55 % Fe) ore types showed some clear removal of almost all silica in between hematite bands to partial removal of silica in the high Fe BIF. Both high-grade BIF and laminated hematite remained with the preserved primary layers of hematite bands that compacted through time due to pressure and folding to form a high-grade bedded iron ore. The space that was occupied by silica is at places filled with thin and scattered recrystallised quartz or goethite matrix. The goethite-rich, friable soft hematite, sometimes in a dark grey powder was formed by the weathering and dissolution of Fe from the BIF by the descending surface or meteoric water. The spatial relationships between the dolerite intrusions and the high-grade hematite ore suggest that the dolerite intrusions caused changes in mineral texture and ore grade. The XRF analysis from the drilled cores showed clear evidence that at closer contacts, hematite orebodies in contact with sills underwent enrichment in Fe and reduction in SiO2. This result shows that aside from secondary supergene enrichment, tertiary Fe enrichment can occur due to igneous activity such as dolerite intrusion
A thesis submitted to the School of Geoscience, Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science in Economic Geology, 2021